Implementation of Taukil Wali at the KUA of Jati District, Kudus Regency from the Perspective of Minister of Religious Affairs Regulation Number 20 of 2019 - Zahro, Almadatus Saekhatus; Rahma, Nabila Luthvita (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The role of the guardian in marriage is an important pillar that must be fulfilled. In the event that the guardian is unable to attend the ceremony, representation can be made by the Head of the Sub-district KUA or Penghulu. The practice of